Sputum host cytokine signatures for diagnosis of TB in children and adults - Mendy, Joseph; Coker, Edward; Weiner, January; van der Spuy, Gian; Chegou, Novel N.; Sutherland, Jayne S. (Frontiers in Immunology, 2025)
BackgroundTuberculosis (TB) still remains the world’s leading infectious disease killer. New screening and diagnostic tests are urgently needed. We have previously identified a 3-marker host protein signature with high accuracy for TB in sputum from adult Gambian patients. The aim of this project was to analyse host sputum markers in a larger cohort of adults and children with presumptive TB from The Gambia, and to determine the global applicability of such a signature in samples from South Africa, Vietnam and Peru.MethodsSputum samples were collected at baseline from all symptomatic participants and used for routine diagnostics and biomarker evaluation. Samples were also collected at 1 and 2 months after anti-TB treatment initiation from those who were subsequently found to have TB. For biomarker evaluation, an aliquot of sputum was digested with an equal volume of Sputolysin®, incubated for 15 minutes at RT, centrifuged, and the supernatant analysed using multiplex cytokine arrays.ResultsFor Gambian participants (n=428 TB and n=313 other respiratory diseases (ORD)) an 8-marker signature was able to differentiate between smear and culture positive TB from ORD with an AUC of 0.77, while a 3-marker signature classified smear negative TB with an AUC of 0.74. Additionally, a 4-marker signature could discriminate between children (<18 years) with TB (n=17) and those with ORD (n=23) with an AUC of 0.87, sensitivity of 82% and specificity of 87%. A 5-marker global signature was identified with an AUC of 0.71.ConclusionThis study describes the use of host markers in sputum for development of a rapid triage test for pulmonary TB in adults and children. Whilst the results are promising for regional-specific and treatment response signatures, our pilot data do not support development of a global test for TB triage based on sputum host signatures.